E-MONEY AS A PAYMENT METHOD: “ANALYSIS OF MATARAM CITY PEOPLE IN USING ELECTRONIC MONEY” - Ilhamdi; Fuad Arif Rahman (International Journal of Islamic and Social Sciences (ISOS), 2021)
The research was conducted with the aim of identifying the factors influencing people's interest in using electronic money (e-money) using a quantitative descriptive approach. The researcher uses the technology acceptance model (TAM) as a conceptual framework that focuses on Perceived Usefulness, Perceived Ease of Use, Perceived Risk, and there are additional variables, namely Customer Attitude (Perceived Benefit) and behavioural intentions to use electronic money. An empirical data test was conducted based on data collected from 384 respondents, reliability analysis (Cronbach's Alpha Coefficient), validity test and multiple regression analysis were conducted to see the relationship between all variables. The final results show that perceived usefulness (PU), perceived ease of use (PEOU), perceived risk (PR), and customer attitudes (CA) have a significant positive effect on people's intentions to use electronic money (E-money).